The Endurance of Sengon (Falcataria moluccana (Miq) Barneby & J.W. Grimes) Seedling against Uromycladium falcatarium Fungus Based on Seed Source and Controller Agent - Tati Suharti; Kurniawati Purwaka Putri; Yulianti Bramasto (Forest Tree Seed Technology Research & Development Center (FTSTRDC)/ Balai Penelitian dan, 2019)
Gall rust disease caused by Uromycladium falcatarium fungus is one of sengon (Falcataria moluccana) diseases in the nursery and field. The purpose of this study was determining the effect of seed sources and controller type against the resistance of sengon seedlings from infection of Uromycladium falcatarium in the nursery. The research design used a factorial completely randomized design with two 2 factors i.e sources of the seed (A1 = seed from the endemic area of gall rust/Kediri; A2 = seed from non-endemic of gall rust/Cianjur) and the type of cotrollers (B1 = no treatment l; B2 = biological fertilizer of Plant Growth Promoting Rhizobacteria (PGPR) (5 g.l-1); B3 = Biofungicide (5 g.l-1); B4 = biofungicide of soursop leaf extract (10 g.l-1); B5 =mancozeb (2 g.l-1). Each treatment combination consisted of 10 seedlings repeated 4 times. The observation variables were the disease incidence and intensity, the number of teliospores and thickness of the epidermal cell wall. The results of the study showed that the interaction of seed sources and type of controller affected the number of teliospores and thickness of the epidermis. The lowest number of teliospores (6.48 teliospores) was found in seedlings from non endemic gall rust areas with the controller of soursop leaf extract. The thickest epidermal cells (5.43 μ - 5.84 μ) were produced from seedlings from gall rust-free area with PGPR solution controller, soursop leaf extract and mancozeb. The disease intensity in seedlings originating from gall-free areas (3.5 percent) is lower than endemic areas (5.2 percent). PGPR and mancozeb were effective to the infection of fungus because the disease incidence and intensity were low after the 3rd control stage.